2010
DOI: 10.1681/asn.2010010049
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosis with Inflammation at One Year Predicts Transplant Functional Decline

Abstract: Lack of knowledge regarding specific causes for late loss of kidney transplants hampers improvements in long-term allograft survival. Kidney transplants with both interstitial fibrosis and subclinical inflammation but not fibrosis alone after 1 year have reduced survival. This study tested whether fibrosis with inflammation at 1 year associates with decline of renal function in a low-risk cohort and characterized the nature of the inflammation. We studied 151 living-donor, tacrolimus/mycophenolate-treated reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 59 publications
8
170
2
Order By: Relevance
“…Biopsies were classified as normal ( 3,12,19 There is also a paucity of literature on late protocol biopsies performed after 12 months in kidney transplant recipients, and our study fills the scarcity of knowledge in this area with our findings that late protocol SAR+IF/TA is significantly associated with rate of eGFR decline over long-term follow-up. Other studies have shown that interstitial fibrosis alone in early protocol biopsy may not predict graft functional decline in allografts with good baseline function; however, ongoing inflammation with interstitial fibrosis leads to graft functional decline, 9 which was also shown in our study where there was increasing percentage of recipients with fibrosis in the inflammation groups in late protocol biopsy and thus the presence of progressive fibrosis in inflamed kidneys predicted graft function. It could be speculated that, although early protocol biopsies are a useful tool, late protocol biopsies more likely have prognostic value in predicting long-term graft function.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Biopsies were classified as normal ( 3,12,19 There is also a paucity of literature on late protocol biopsies performed after 12 months in kidney transplant recipients, and our study fills the scarcity of knowledge in this area with our findings that late protocol SAR+IF/TA is significantly associated with rate of eGFR decline over long-term follow-up. Other studies have shown that interstitial fibrosis alone in early protocol biopsy may not predict graft functional decline in allografts with good baseline function; however, ongoing inflammation with interstitial fibrosis leads to graft functional decline, 9 which was also shown in our study where there was increasing percentage of recipients with fibrosis in the inflammation groups in late protocol biopsy and thus the presence of progressive fibrosis in inflamed kidneys predicted graft function. It could be speculated that, although early protocol biopsies are a useful tool, late protocol biopsies more likely have prognostic value in predicting long-term graft function.…”
Section: Discussionsupporting
confidence: 79%
“…7 Interstitial fibrosis and/or tubular atrophy on its own do not predict long-term renal allograft survival, but the combination of inflammation and fibrosis has been shown to be a surrogate marker for progressive graft functional decline. 8,9 Therefore, it becomes critical to examine the predictive ability of histologic abnormalities in early and in late protocol biopsies on long-term renal allograft function.…”
Section: Introductionmentioning
confidence: 99%
“…However, the related increased interstitial inflammation by IL-17A-producing CD4 + T cells observed in these biopsies suggests an ongoing persistent chronic alloimmune response, resulting in increased presence of inflammatory infiltrates and interstitial fibrosis and more senescence. Previous studies demonstrated that concomitant interstitial fibrosis and inflammation in protocol biopsies obtained in the first year correlates with later allograft dysfunction and loss [25]. Finally, belatacept treatment allowed maintaining a stable number of FoxP3 + cells at tissue level which, in turn, could contribute to preserve in-situ tolerance mechanisms [26].…”
Section: Discussionmentioning
confidence: 96%
“…Studies of mRNA and miR in kidneys with fibrosis reveal that many molecular changes associated with fibrosis are related to inflammation and matrix remodeling (21)(22)(23)(24)(25). We previously reported that fibrosis in human kidney transplants was associated with transcripts expressed in certain inflammatory cells: mast cell transcripts (MCATs) such as carboxypeptidase 3 (CPA3) (26) and immunoglobulin transcripts (IGTs) representing plasma cells (27).…”
Section: Funding Canada Foundation For Innovation and Genome Canadamentioning
confidence: 99%